2011
DOI: 10.1111/j.1747-0803.2010.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Closure of Secundum Atrial Septal Defect in Infants Less than 12 Months of Age Improves Symptoms of Chronic Lung Disease

Abstract: Transcatheter closure of atrial septal defects in infants can be safe, effective, and may be indicated for situations in which the left to right shunt may be implicated as a cause of ongoing chronic lung disease. Moderate increases in pulmonary blood flow due to atrial septal defects may have a negative clinical impact regarding continuing respiratory insufficiency in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 28 publications
2
26
1
1
Order By: Relevance
“…Plausibly one could speculate that ASDs might offer a survival benefit in very/extremely premature infants with pulmonary hypertension. However this hypothesis is contrary to several prior reports suggesting that larger ASDs actually exacerbate underlying chronic lung disease of prematurity 22,23 . It is unclear why isolated pulmonary stenosis may confer an improvement in survival.…”
Section: Discussioncontrasting
confidence: 99%
“…Plausibly one could speculate that ASDs might offer a survival benefit in very/extremely premature infants with pulmonary hypertension. However this hypothesis is contrary to several prior reports suggesting that larger ASDs actually exacerbate underlying chronic lung disease of prematurity 22,23 . It is unclear why isolated pulmonary stenosis may confer an improvement in survival.…”
Section: Discussioncontrasting
confidence: 99%
“…Epidemiologically, ASDs account for 8–10% of congenital heart defects, though the majority of these close spontaneously in the first year of life [26]. For those with persistent defects, small studies have suggested that infants with BPD may have improved respiratory outcome following transcatheter closure of left-to-right shunts at approximately 6 months of age [27, 28]. Unfortunately, our finding that ASDs were associated with PH development is difficult to interpret causally.…”
Section: Discussionmentioning
confidence: 98%
“…In cases of PDA with high PVR and right to left shunting initial treatment with PH drugs followed by a second hemodynamic evaluation is advised. In the case of ASD, although the percutaneous closure of ASD has been published in BPD infants with good results the high rate of spontaneous closure or decrease in the size of the defect in the first months of life should be considered.…”
Section: Discussionmentioning
confidence: 99%